Dose-response relationship in patients with liver metastases from neuroendocrine neoplasms undergoing radioembolization with 90Y glass microspheres: brief communication - Watanabe, Masao; Leyser, Stephan; Theysohn, Jens; Schaarschmidt, Benedikt; Ludwig, Johannes Maximilian; Fendler, Wolfgang P.; Moraitis, Alexandros; Lahner, Harald; Mathew, Annie; Herrmann, Ken; Weber, Manuel (Journal of nuclear medicine, 2024)
The benefit of multicompartment dosimetry in the radioembolization of neuroendocrine neoplasms is not firmly established. We retrospectively assessed its potential with patient outcome. Methods: Forty-three patients were eligible. The association of mean absorbed dose (MAD) for tumors and treatment response was tested per lesion with a receiver operating characteristic curve analysis, and the association of MAD with progression-free survival (PFS) and overall survival was tested per patient using uni- and multivariate Cox regression analyses. Results: The area under the curve for treatment response based on MAD was 0.79 (cutoff, 196.6 Gy; P < 0.0001). For global PFS, grade (grade 2 vs. 1: hazard ratio [HR], 2.51; P = 0.042; grade 3 vs. 1: HR, 62.44; P < 0.001), tumor origin (HR, 6.58; P < 0.001), and MAD (HR, 0.998; P = 0.003) were significant. For overall survival, no prognostic parameters were significant. Conclusion: In line with prior publications, a MAD of more than 200 Gy seemed to favor treatment response. MAD was also associated with PFS and may be of interest for radioembolization planning for neuroendocrine neoplasm patients.